LQR Control for Experimental Double Rotary Inverted Pendulum - Tran, Nhat-Cuong; Nguyen, Van-Dong-Hai; Le, Chi-Thanh; Lai, Anh-Hai; Nguyen, Trong-Phung; Huynh, Minh-Tuan; Phan, Viet-Thanh; Tong, Gia-Dat; Nguyen, Le-Thanh-Dat; Ngo, Trinh-Anh-Tuan (Journal of Fuzzy Systems and Control, 2024)
LQR control and rotary inverted pendulum (RIP) are already a classic and typical category in the field of automatic control algorithms. From the experience of a 1-order system, we study and apply the LQR algorithm to the 2-step system (DRIP – Double Rotary Inverted Pendulum). In this study, the authors will present kinematic equations of the DRIP system, the method of building an LQR controller for the system in the balance position of bar 1 upwards bar 2 downwards (the first pendulum balances at 0, the second pendulum balances at 180) and build a practical model to investigate the stability of the system. Our method is proven to balance one link well and anti-fluctuation another link well for this model through both simulation and experiment.